The application of gray system-variable fuzzy sets coupling theory on the susceptibility assessment of debris flow hazards - Zhang, Xue-Jun; Gu, Xin-Bao (Frontiers in Earth Science, 2023)
The occurrence of debris flow hazards has significant destructive effects on the life and property safety of the people, so the risk assessment of debris flow hazards has great significance.The maximum amount of debris flow at one time (X1), the reserves of loose substance(X2), the watershed area(X3), the length of the ditch(X4), the relative height difference(X5), the gradient of side slope(X6), longitudinal slope of main ditch(X7), the length ratio of replenishment section(X8), the daily maximum rainfall(X9) and Faults developed in the watershed(X10) are selected as the evaluation index at first. Then the gray system-variable fuzzy sets coupling model is introduced; secondly, the relative membership degree matrix about the fuzzy variable sets is established, and the weight coefficients considering the uncertainty of assessment indices are determined based on the Entropy weight method; finally, the susceptibility level of debris flow hazards is determined using the mean ranking feature value. The conclusions are drawn that the results obtained based on the coupling technique are consistent with the current specification; its accuracy arrives at 83%, and the method is feasible for the susceptibility level assessment of debris flow hazards; compared to the traditional variable fuzzy sets model, it avoids the uncertainty of magnitude in the standard analysis, and it can ensure the objectivity and accuracy of the calculation result, and its calculation process is simple and efficient. In total, the findings of the proposed model provide an alternate way to assess the susceptibility level of debris flow hazards and improve the evaluation accuracy in the future.